SOCRATES Invades Central Europe - Slowinski, Joseph (Education Policy Analysis Archives, 1998)
The objective of this article is to explore the current reality faced by higher education students in Central and Eastern Europe and to draw out the implications of this current reality for policy makers in the future. In the article, I explore the influence of transnational corporations' training programs on education as it currently pertains to Central and Eastern European higher education and employment. In addition, multinational corporate entities exercise influence on European Union policy through the role of lobby organizations and activities. I explore the influence of these practices on education with an emphasis on the emerging importance of Western language skills. In addition, I focus on the European Union and its efforts to expand into Central and Eastern Europe in order to provide a focal point for analysis.